2007
DOI: 10.1007/s11104-007-9498-8
|View full text |Cite
|
Sign up to set email alerts
|

Seed water status and root tip characteristics of two annual grasses on lichen-dominated biological soil crusts

Abstract: Biological soil crusts can affect seed germination and seedling establishment. We have investigated the effect of biological soil crusts on seed water status as a potential mechanism affecting seed germination. The seed water potential of two annual grasses, one exotic Bromus tectorum L. and another native Vulpia microstachys Nutt., were analyzed after placing the seeds on bare soil, on a crust that contains various lichens and mosses (mixed crust), or on a crust dominated by the crustose lichen Diploschistes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
30
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 40 publications
5
30
1
Order By: Relevance
“…Most studies from many different climate zones show biocrusts either a positive or neutral effect (Li et al 2005;Deines et al 2007;Serpe et al 2008). For instance, in a cool desert, Harper and Pendleton (1993) found plants growing in biocrusts had four times greater biomass than those in uncrusted soils.…”
Section: Plant Shoot Height and Ending Biomassmentioning
confidence: 99%
“…Most studies from many different climate zones show biocrusts either a positive or neutral effect (Li et al 2005;Deines et al 2007;Serpe et al 2008). For instance, in a cool desert, Harper and Pendleton (1993) found plants growing in biocrusts had four times greater biomass than those in uncrusted soils.…”
Section: Plant Shoot Height and Ending Biomassmentioning
confidence: 99%
“…Escudero et al (2007) and Serpe et al (2008) showed that BSC reduced seedling emergence when it was dominated by species like Diploschistes sp., because this lichen might seal the soil, thus reducing water availability during the germination period of some plants (Otsus and Zoel, 2004;Morgan, 2006). Contrastingly, the presence of both algal and moss crusts significantly enhanced the germination of Bassia dasyphylla (Fisch.…”
Section: Discussionmentioning
confidence: 99%
“…reduced plant emergence (Escudero et al, 2007;Serpe et al, 2008). This might be due to the sealing of the soil pores by these crusts that might reduce water availability and thus inhibit germination (Eldridge et al, 2010).…”
mentioning
confidence: 99%
“…In addition to detrimentally affecting nitrogen budgets, the destruction removes what I term here the ' fi rst line of defence ' against cheatgrass proliferation (Kaltenecker et al 1999 ). Members of the crust, principally the crustose lichen Diploschistes muscorum and the moss Bryum argenteum , delay or largely thwart the establishment of cheatgrass (Deines et al 2007 ;Serpe et al 2006Serpe et al , 2008. For D. muscorum , key in its role is the physical barrier this cryptogam ' s thalli create to root penetration by seedlings.…”
Section: Restoration and M Aintenance Of The B Iological S Oil C Rustmentioning
confidence: 99%
“…It reserves its greatest kudos, however, for those who heed the warnings and take concrete steps to turn back disasters, such as the invasion of cheatgrass. mesic water status ( − 0.6 MPa) on bare soil (Serpe et al 2008 ). Admittedly, the biological soil crust in any community is not composed entirely of crustose lichens or B. argenteum , or both.…”
Section: Restoration and M Aintenance Of The B Iological S Oil C Rustmentioning
confidence: 99%